COMMUNICATION OF TEACHERS AND STUDENTS IN LEARNING DURING THE COVID-19 PANDEMIC AT SMP N 1 LAUBALENG - ribka hernita sitepu; nathanael sitanggang; joharis lubis (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
This study aims to determine the communication of teachers and students in learning in a virtual classroom at SMP N 1 Laubaleng. The Covid-19 pandemic of course makes us limit all interactions and also maintain distance between each other, even communication is hampered, including communication between teachers and students at SMP N 1 Laubaleng. This research uses quantitative research with descriptive format. In analyzing the data, the writer uses techniques, namely, data collection techniques, namely observation, documentation and interviews. This interview as supporting data for the main data of the SPSS test from the results of the questionnaire answers that have been distributed to students. In this study, primary data was obtained through filling out a questionnaire by 101 students studying social studies at SMP N 1 Laubaleng. In this study there are 2 variables, namely: Free Variable, namely Online Learning (X) and Bound Variable, namely Student Learning Achievement (Y). The results showed that, the communication between teachers and students of SMP N 1 Laubaleng was in the medium category. Student learning activities in social studies subjects are also in the medium category. In addition, there is a significant positive effect between teacher and student communication on student learning behavior.